Serological markers predict inflammatory bowel disease years before the diagnosis. Issue 5 (26th July 2012) - van Schaik, Fiona D M; Oldenburg, Bas; Hart, Andrew R; Siersema, Peter D; Lindgren, Stefan; Grip, Olof; Teucher, Birgit; Kaaks, Rudolf; Bergmann, Manuela M; Boeing, Heiner; Carbonnel, Franck; Jantchou, Prevost; et al.
Abstract : Objective: Anti-neutrophil cytoplasmic antibodies and anti- Saccharomyces cerevisiae mannan antibodies (ASCAs) have been detected in the serum of patients with ulcerative colitis (UC) and Crohn's disease (CD) and their unaffected family members. The aim of this study was to establish the value of serological markers as predictors of UC and CD. Design: Individuals who developed CD or UC were identified from the European Prospective Investigation into Cancer and Nutrition (EPIC) study. At recruitment, none of the participants had a diagnosis of CD or UC. For each incident case, two controls were randomly selected matched for centre, date of birth, sex, date of recruitment and time of follow-up. Serum of cases and controls obtained at recruitment were analysed for ASCA IgG, ASCA IgA, perinuclear anti-neutrophil cytoplasmic antibody (pANCA), antibodies against Escherichia coli outer membrane porin C (OmpC) and flagellin CBir1. Conditional logistic regression was used to determine risk of CD and UC. Receiver operating characteristic curves were constructed to test accuracy. Results: A total of 77 individuals were diagnosed with CD and 167 with UC after a mean follow-up of 4.5 (SD 3.2) and 4.4 (SD 3.1) years following blood collection, respectively. Combinations of pANCA, ASCA, anti-CBir1 and anti-OmpC were most accurate in predicting incident CD and UC (area under curve 0.679 and 0.657, respectively). The predictive value of the combination of markers increased when time to diagnosis of CD or UC decreased. Conclusion: A panel of serological markers is able to predict development of CD and UC in individuals from a low-risk population.